Integrative Framework of James A. Banks and Kamanto Sunarto’s Multicultural Education for Preventing SARA Conflicts in Indonesia - Chandra Dwisetyo Widodo; Abdul Latief Hilmy; Rifki Rosyad (Badan Litbang dan Diklat Kementerian Agama RI, 2026)
Indonesia’s cultural, ethnic, and religious diversity is a national strength, yet it also creates vulnerabilities that can trigger SARA-based tensions, particularly when intensified by digital misinformation and the politicization of identity. This study responds to the need for a multicultural education framework that bridges global theoretical perspectives with Indonesia’s socio-religious realities. Employing a qualitative analytical approach, the research integrates James A. Banks’ multidimensional model of multicultural education with Kamanto Sunarto’s perspective, which emphasizes inclusivity rooted in Islamic intellectual traditions. The findings reveal that Banks’ focus on educational integration and equity aligns closely with Sunarto’s emphasis on interreligious and intercultural openness, producing a complementary model suited to mitigating SARA-related conflicts. This integrated framework provides fresh direction for curriculum development, teacher capacity-building, and interfaith educational programs, while offering practical contributions to efforts aimed at strengthening social harmony in Indonesia. ABSTRAK Keberagaman budaya, etnis, dan agama adalah kekuatan Indonesia, namun pada saat yang sama menjadi sumber munculnya ketegangan SARA, terutama ketika diperuncing oleh arus informasi digital dan politisasi identitas. Penelitian ini berangkat dari kebutuhan akan sebuah kerangka pendidikan multikultural yang mampu menjembatani teori global dengan realitas sosial Indonesia. Dengan pendekatan kualitatif-analitis, studi ini menggabungkan gagasan James A. Banks tentang pendidikan multikultural multidimensional dengan perspektif Kamanto Sunarto yang menekankan nilai-nilai inklusivitas dalam tradisi Islam. Hasil analisis menunjukkan bahwa penekanan Banks pada integrasi dan keadilan pendidikan berpadu secara komplementer dengan fokus Sunarto pada keterbukaan lintas agama dan budaya. Keduanya kemudian membentuk model yang relevan untuk meredam potensi konflik SARA. Kerangka ini menawarkan arah baru bagi pengembangan kurikulum, peningkatan kompetensi guru, serta program dialog antariman, sekaligus memberikan kontribusi nyata bagi upaya memperkuat harmoni sosial di Indonesia.